A case of Helicobacter pylori-negative early gastric adenocarcinoma with gastrointestinal phenotype - Takatsuna, Masafumi; Azumi, Rie; Mizusawa, Takeshi; Sato, Hiroki; Mizuno, Ken-Ichi; Kato, Takashi; Yokoyama, Junji; Ajioka, Yoichi; Terai, Shuji (Endoscopy International Open, 2021)
A 40-year-old man with slightly depressed (0-IIc) type gastric cancer of the pyloric anterior gastric area underwent pre-operative screening for tetralogy of Fallot and endoscopic submucosal dissection (ESD) and was tested for Helicobacter pylori antigens and antibodies. Both tests were negative. He did not have a history of eradication. Pathological diagnosis of ESD showed a well-differentiated adenocarcinoma. The tumor was CD10-positive, MUC5AC-negative, and MUC6-confocal positive; it showed differentiation with gastrointestinal phenotype. Moreover, the tumor cells were lysozyme-positive, resembling Paneth cells. Mucosal glands exhibited intestinal metaplasia on the anal side of the tumor lesion. On the oral side of the tumor, metaplasia was non-existent, with normal pyloric glands present in the mucosal layer. The patient was not infected with H. pylori; however, intestinal metaplasia existed around the early gastric cancer. This suggested that the intestinal metaplasia occurred due to bile reflux, and the gastric neoplasia arose with the metaplasia without an H. pylori infection. This case may potentially help explain gastric cancer development in the absence of H. pylori infection.